IoT Based Hydroponic Water Nutrient and pH Monitoring with Real-Time Notifications - Tri Agusti Farma; Dora Palupi; Weri Sirait (Politeknik Negeri Cilacap, 2025)
Indonesia is an agricultural country whose population lives from the agricultural sector, the Government has encouraged agriculture to realize the use of modern technology for the agricultural sector which is useful for increasing farmer productivity and making farmers' work easier with quality harvests, as well as more efficient food security in Indonesia. One way to save time and energy for farmers to find out nutrients and pH is by using a nutrient and pH monitoring system for hydroponic plant water. The purpose of this research is to create an IoT-based automatic system, used for systematic real-time monitoring of water nutrients in hydroponic plants using a TDS sensor to measure the mass weight of nutrients and a pH meter to measure the acidity of water, a DHT22 sensor to measure temperature and humidity, and a DSB18B20 sensor to measure water temperature, the data obtained from these sensors will be displayed on the LCD. The final result of the tool created is a nutrient and pH monitoring system for water in pakcoy plants, the results of sensor readings will be sent in real-time to the dashboard and WhatsApp. This research method uses the R and D (Research and Development) method with the ADDIE (analyze, design, develop, implement, evaluate) model. The IoT expert validation value was 0.91 (very appropriate) and the farmer effectiveness validation value was 0.85 (very effective). The outputs generated from this research can be used to make it easier for hydroponic farmers to monitor plant nutrient balance automatically and systematically.